Direct Measurement of the Isomerization Barrier of the Isolated Retinal Chromophore1. Issue 16 (10th March 2015) - Dilger, Jonathan; Musbat, Lihi; Sheves, Mordechai; Bochenkova, Anastasia V.; Clemmer, David E.; Toker, Yoni
Abstract Isomerizations of the retinal chromophore were investigated using the IMS‐IMS technique. Four different structural features of the chromophore were observed, isolated, excited collisionally, and the resulting isomer and fragment distributions were measured. By establishing the threshold activation voltages for isomerization for each of the reaction pathways, and by measuring the threshold activation voltage for fragmentation, the relative energies of the isomers as well as the energy barriers for isomerization were determined. The energy barrier for a single cis–trans isomerization is (0.64±0.05) eV, which is significantly lower than that observed for the reaction within opsin proteins.